Impacts of COVID-19 on Ecotourism: A Study in Bijilo Monkey Forest and Kachikally Crocodile Pool, The Gambia - Sambou, Omar; Marjono, Marjono; Ciptadi, Gatot; Putra, Fadillah (Graduate School, Universitas Brawijaya, 2023)
Most people agree that COVID-19 has affected the tourism sector the most. This paper seeks to find the socioeconomic impacts of COVID-19 on the destination under study. The research implored semi-structured interviews, observations, and content analysis to acquire information. The first case of the virus in The Gambia was registered on the 16th of March 2020. As of the 29th of January, 2021, the country registered 4,090 positive cases of COVID-19, out of whom 3,792 have recovered, 128 are confirmed to have died, and 170 active cases. A total of 59% of confirmed cases are male and 41% female. The ecotourism industry of The Gambia is hit hard by the impacts of COVID-19. The places highly affected are the wildlife ecologies with no spiritual connections. There is evidence of wildlife crime and negative human-wildlife interaction. Sacred sites are easier to manage as people’s spirituality frowns at wildlife cruelty. The pandemic has caused severe economic, health, and social challenges in the Gambia, killing many and disrupting the normal functioning of society, including wildlife ecologies in some places. It has increased wildlife hunger in Kachikally Crocodile Pool, economic distress, and human-wildlife conflict in Bijilo Monkey Forest and surrounding. Keywords: Covid-19, Ecotourism, Environment, impacts, socio-economic.